L
2 a
(RAx2 — MAx1)dx1 + | (--qax2 — 3 MAa — 6 qa3 + 9RAa2 + 6 qa2x2 — 3aRAx2 1
+ ^^x2 + ^4X2 + 2qa2x2 — 3RAa ■ x2 — 2qax2 + RAx2)dx2 113
-RAa3 — -MAa2 — — qa- 8a3 — 3MA ■ 2a — 6qa3 ■ 2a + 9RAa2 ■ 2a + 3qa2 ■ (2a)2 3 2 6
--a ■ RA ■ 4a2 + - q ■ 16a4 +-MA ■ 4a2 H---2oa2 ■ 4a2---3^a ■ 4a2
2 8 2 2 2
— — ■ 2qa ■ 8a3 + - RA ■ 8a3 3 w 3 A
- 2M4 ~YqU = °
Rozwiązujemy układ równań „3 i 4
9
^ /^a + 3M4 + — qa2 = 0/x2
9RAa--MA - ~jqa - 0
8 .
—9 RAa + 6 Ma +-qa2 — 0
9RAa--MA - ~jqa - 0
2 ma ~2qa2 = 0
Ma = -qa2
8 9
—9RAa + 6M4 + - qa2 = 0
8 9
—9 RAa = —6Ma —-qa2 16
R4 = —qa A 27H
Rozwiązujemy układ równań „1 i 2’
Ra — 2 qa + Rb — 0